Quantitative and intelligent risk models in risk management for constructing software development projects: A review - Burairah, Hussin; Abdelrafe, Elzamly (SERSC (Science & Engineering Research Support Society), 2016)
Techniques and models for mitigating risk in software development projects classified into three categories–namely, qualitative, quantitative, and intelligent approaches. This paper is to review the quantitative and intelligent risk models in software risk management for software development projects. Indeed, this area needs more effort from scholars and researchers in quantitative and intelligent risk models to mitigate risks. As future work, we will use these hybrid models of quantitative and intelligent for mitigating software risks in cloud computing such as neural network, genetic algorithm and others artificial intelligence techniques.